Optimization of loading facilities at the terminal - Bagdonienė, Danutė (Transport, 2008)
The problems of stock management and proper choice of transport facilities are defined and analysed taking into account the relationship between cost of transportation and vehicle’s capacity and size of cargo lots. By using mathematical statistical methods, the optimal vehicle’s capacity for a particular lot on the routes for taking the cargo out as well as the periodicity of cargo delivery are determined. First published online: 27 Oct 2010